Epidemiology and outcomes of tibial plateau fractures in adults aged 60 and over treated in the United Kingdom. Issue 6 (June 2022) - Donovan, Richard L.; Smith, James R.A.; Yeomans, Daniel; Bennett, Fenella; White, Paul; Chesser, Tim J.S.
Highlights: Tibial plateau fractures account for 8% of all fractures in older adults. Management is relatively conservative when compared with younger cohorts. Reoperation occurred in 11% of patients and was related to postoperative complications and high degrees of joint depression. Abstract: Background: Tibial plateau fractures are common in older adults, often resulting from low-energy falls. Although lower limb fragility fracture care has evolved, the management of tibial plateau fractures in older patients remains poorly researched. This study aimed to define the epidemiology, treatment and outcomes of tibial plateau fractures in patients aged over 60 years. Methodology: Patients aged 60 years or older with a tibial plateau fracture who presented to a single trauma center between January 2008 and December 2018 were identified. Incomplete records were excluded. Epidemiological data, fracture classification, injury management, radiological outcomes, complications, and mortality were assessed via retrospective case note and radiograph review. Local ethics approval was obtained. Results: Two-hundred and twenty patients with a mean age of 74 years (range 60–100) were included. 73% were female and 71% of injuries were sustained following low-energy falls. Median follow up was three months. 50% of fractures involved the lateral plateau. 60% of injuries were treated non-operatively. 76% of patients had their weight-bearing restricted for the first six weeks, with little difference between operatively and non-operatively managed patients. 8% of all patients required subsequent knee replacement. All-cause mortality at 30-days and one-year were 2% and 5% respectively. Conclusion: The majority of tibial plateau fractures in the over 60s are sustained from low-energy trauma. Management is relatively conservative when compared with younger cohorts. The data reported brings up questions of whether surgical treatment is beneficial to this patient group, or whether restricted weight bearing is either possible or beneficial. Prospective, multi-center comparative trials are needed to determine whether increased operative intervention or different rehabilitation strategies purveys any patient benefit.